Kesantunan Imperatif pada Kesenian Senjang Musi Banyuasin - Putra, Ardiansyah Pratama; Masnunah, Masnunah; Nufus, Hayatun (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research was conducted to answer the problem of what are the types of imperative politeness and how is imperative politeness in the art of Senjang Musi Banyuasin. The purpose of the study is to describe the types and politeness imperatives that exist in the art of Senjang Musi Banyuasin. The method used is descriptive qualitative, the results of the study there are 22 imperative utterances that use language politeness strategies. There are two types of imperative speech functions of orders and prohibitions as well as eight forms of imperative politeness speech including (1) orders, (2) requests, (3) requests, (4) invitations, (5) prohibitions, (6) expectations, (7) suggestions, and (8) congratulation. In addition, there is the application of Leech's politeness principle, the maxim of wisdom, acceptance (praise), humility, compatibility, sympathy and the application of the scale of choice and indirectness. It is hoped that further researchers will examine language politeness in speech communities in various regions which are then associated with the culture of the local community.